(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With easier and faster internet access nowadays, social media has become an important means of online marketing activities. Both individuals and companies carry out activities on online platforms and develop business opportunities using social media. Meanwhile, there has been a lot of research on social media and discussing the effects of social media marketing activities. Researchers want to see the effect of social media marketing activities on purchase intentions by mediation of brand equity and customer trust in the healthy food industry. To empirically test the effect of marketing activities on social media, researchers conducted a survey of 151 social media users to perform data analysis. The results of data analysis shows that social media marketing indirectly affect the buying interest through brand equity and customer trust. At the same time, brand equity and customer trust influence buying interest. In the end, the academic and management implications based on the empirical results of this study serve as a reference for healthy food to increase the social media marketing activities.